Dissemination of eco-friendly rat repellent devices to farmer groups in Serang City - Wahyu Sejati; Daisman Purnomo Bayyu Aji; Tjhwa Endang Djuana; Putri Aida Azizah Rahmah; Nawang Wulan; Dinda Ayu Pakungwati; Maharani Alichya; Nuzul Rizky Zayat Rahawarin (Community Empowerment, 2024)
Rats pose a significant threat to rice farmers, attacking crops at all stages of growth, including storage, with the most severe damage occurring during the reproductive phase. In Bendung Village, Bendung District, rats have caused substantial losses, including crop failures, particularly due to unpredictable weather conditions. The proposed solution involves creating eco-friendly rodent repellents powered by solar energy. The activities include socialization, device design, technology implementation, and evaluation. Evaluation results indicate that 40% of farmers understand the operation of the rodent repellents using frequency waves, and 60% understand their environmental impact. This program has provided farmers with new knowledge about methods to repel harmful rodents.